Dendrochronology as a source of data for landslide activity maps – an example from Beskid Żywiecki Mountains (Western Carpathians, Poland) - Łuszczyńska Katarzyna; Wistuba Małgorzata; Malik Ireneusz (Environmental & Socio-economic Studies, 2017)
We applied dendrochronological methods for dating landslide activity in the study area (3.75 km2), on the slopes of Sucha Mountain (1040 m a.s.l.), in the Beskid Żywiecki Mountains, in the Western Carpathians. 46 sampling sites were distributed throughout the study area. At each site we sampled 1-3 coniferous trees: Norway spruces (Picea abies Karst.) and/or silver firs (Abies alba Mill.). From each tree 2 cores were sampled: one from the upslope and the other from the downslope side of the stem. Based on tree-ring widths measured for opposite sides of stems we have calculated eccentricity index values and dated past landslide events. Mean frequency of landslides was obtained for each sampling site. Finally, the data was interpolated into a map of landslide activity. Inverse Distance Weighting (IDW) interpolation has been applied. For most of the study area we found medium (19 sites) and low (23 sites) levels of landslide activity. The highest level of activity was recorded for the largest landslide slope and for the one small landslide. The study conducted on Sucha Mountain has shown that dendrochronology can be an effective method for analysing landslide activity and may be useful in further studies, including those for landslide hazard and risk assessments.